DAKWAH DIGITAL DAN GENERASI MILENIAL (Menelisik Strategi Dakwah Komunitas Arus Informasi Santri Nusantara) - Athik Hidayatul Ummah (TASÂMUH, 2020)
Advances in digital technology and the use of social media have increasingly led to implications, including in religious life. Religious references make the internet as a source. While internet users in Indonesia are dominated by millennials who have an open and rational mind. They make the internet as an alternative source of knowledge, including religious knowledge. Digital da'wah is a model of Islamic teaching through digital media or social media which has advantages, it’sneeds of the audience, instant feedback, practical and efficient. Digital da'wah was created by the AIS Nusantaravirtual community makes a new perspective in utilizing social media for da'wah. This article explains how the strategy of the AIS Nusantara virtual community in building Islamic narratives in the style of santri and pesantren for millennials through digital spaces. Various strategies for send information was designedmore eye-catching and modern format. Digital da'wah has managed by santri is the right model of da'wah cause of many preachers and da’wah material that does not have a sanad or teacher. The rise of santri and pesantren in cyberspace is proof that santri have begun to realize that digital da’wah is important.